Infrared and microwave drying methods on the rehydration behaviour and mass transfer diffusion coefficient of Loligo vulgaris - Ozyalcin, Zehra Ozden; Kipcak, Azmi Seyhun (YILDIZ TECHNICAL UNIV, 2023)
In this study, the effect of various drying methods on the rehydration behaviour and mass transfer diffusion coefficients of squid (Loligo vulgaris) is investigated. Drying methods were selected as infrared (IR), ultrasonic pre-treated infrared (US-IR) and microwave (MW). In IR and US-IR method drying temperatures were within 60 - 80 degrees C and in MW drying the power levels were in between 140 - 350 W. The rehydration process was carried out for all samples in 180 minutes at room temperature with 30-minute weighing intervals. Obtained rehydration data were applied to the mathematical models of Peleg and Two-Term Exponential. The rehydration ratios were changed between 1.78 - 2.50, 1.91 - 2.66 and 2.78 - 3.83 g/g dry matter for IR, US-IR, and MW respectively. Mass transfer diffusion coefficients of effective moisture diffusion (Deff) values were changed between 1.01 x 10-7 - 1.07 x 10-7, 1.02 x 10-7 - 1.08 x 10-7, and 1.12 x 10-7 - 1.22 x 10-7 m2/s, for IR, US-IR, and MW respectively. Peleg and TwoTerm Exponential mathematical models showed matched well with the experimental data. In addition, colour values found to be changed particularly in the brightness values due to rehydration process.
Keywords: Colour; Effective Moisture Diffusion Coefficient; Rehydration Ratio; Seafood; Squid; KINETICS; ULTRASOUND; PRETREATMENTS; TEMPERATURE; COLOR; Engineering